VECTOR medium voltage switchgear entry plan to Swedish and Norwegian markets : Multiple case study VEO Oy - Söderholm, Lauri (My University, 2020)
The purpose of this thesis is to study the purchasing processes, supplier selection criteria and in more detail the local presence criterion in the Swedish and Norwegian markets. This leads to the research question of: “What is the purchasing process like in Sweden and Norway, and what is the suitable level of local presence?” The study is done for VEO, for their medium voltage switchgear product sales. Many different purchasing models are found to have many parts of the structure in common, while emphasis of some parts differ. The purchasing process is affected by a multitude of factors: environmental, organizational, group and individual forces. There are many different criteria considered by purchasers when choosing a supplier. The information can be found from many sources, and different criteria are evaluated in different parts of the purchasing process. The local presence criterion can be analyzed through different entry modes. There are different approaches to choosing an entry mode and many factors affecting the choice. The entry modes analyzed in this study are limited to those possibly suitable for this situation. The different entry modes, and thus levels of local presence, offer varying advantages and disadvantages. The research approach of this study is deductive mono-method qualitative research. I will be conducting an explanatory study through questionnaire interviews. The sample consists of 6 companies, 4 from Sweden and 2 from Norway. These companies are of different types, end-users either in industry or utilities, system integrators or consultants, with one public company in both markets. The interview is conducted via Microsoft Forms questionnaire. The analysis section consists of a brief analysis of the markets and an in-depth analysis of the results. The analysis of the markets includes brief description of the economic situations of the markets and industries, and a brief description of the worst competitors. The results showed little difference between the markets. The most significant difference is the apparent need for more local presence and more known supplier by the Norwegian companies. The basic structure of the purchasing process is similar in each company, but the emphasis differed, and after-purchase operations are included by only two interviewees. Price is found to be the most important factor for purchasing decision, with delivery as the second-most important factor. The people responsible for the purchasing function are quite similar. End-users have purchasing professionals in charge, while system integrators have project professionals. Consultants are not that involved in the purchasing process. The local presence section offers varying results, since two of the answers are no local presence, one is local partner presence and three are local subsidiary presence. The study offers many practical results, but the generalizability of it could be better. The relatively low number of companies as well as the wide variety of different types, does not offer possibility for in-depth analysis, but it gives a general picture of the subjects in the markets. Further research could be conducted on a general level with significantly more companies, or by focusing on one type of company to gain more in-depth understanding of individual company types.
Keywords: purchasing; suppliers; purchase decisions; supplier selection criteria; purchasing process; decision-making unit; entry modes; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business